2021
DOI: 10.1186/s13550-021-00833-3
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and harms of implementing [18F]FDG-PET/CT for diagnosing recurrent breast cancer: a prospective clinical study

Abstract: Background [18F]-fluorodeoxyglucose-positron emission tomography/computed tomography ([18F]FDG-PET/CT) has been implemented sporadically in hospital settings as the standard of care examination for recurrent breast cancer. We aimed to explore the clinical impact of implementing [18F]FDG-PET/CT for patients with clinically suspected recurrent breast cancer and validate the diagnostic accuracy. Methods Women with suspected distant recurrent breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…29 Moreover, a study that evaluated the benefits of PET-CT for the diagnosis of recurrent breast cancer has reported detecting an incidental second primary malignancy in 4% of patients. 30 Similarly, a recent study reported that PET-CT revealed a suspected metachronous second primary malignancy in 37 of 233 breast cancer female patients. 12 When reviewing the cases presented in our report, two of the three cases of second primary malignancies would have been discovered, had the patients undergone the proper screening tests for other malignancies, regardless of the diagnosis of breast cancer.…”
Section: Discussionmentioning
confidence: 94%
“…29 Moreover, a study that evaluated the benefits of PET-CT for the diagnosis of recurrent breast cancer has reported detecting an incidental second primary malignancy in 4% of patients. 30 Similarly, a recent study reported that PET-CT revealed a suspected metachronous second primary malignancy in 37 of 233 breast cancer female patients. 12 When reviewing the cases presented in our report, two of the three cases of second primary malignancies would have been discovered, had the patients undergone the proper screening tests for other malignancies, regardless of the diagnosis of breast cancer.…”
Section: Discussionmentioning
confidence: 94%
“…Before initiating first-line treatment, patients had a combined 2-[ 18 F]FDG-PET/CT performed with CE-CT at baseline to diagnose MBC 16 , 17 . 2-[ 18 F]FDG-PET/CT and CE-CT were performed simultaneously for each follow-up scan, but treatment decisions were based on CE-CT without knowledge of 2-[ 18 F]FDG-PET images.…”
Section: Methodsmentioning
confidence: 99%
“…Another study by Hildebrandt et al, showed that, in 100 patients with suspected recurrence, the area under the receiver operating curve for distant recurrence was 0.99 for FDG PET-CT, 0.84 for contrast-enhanced CT, and 0.86 for the combination of contrast-enhanced CT and bone scintigraphy [50]. Vogsen et al, in a prospective study of 225 patients with suspected breast cancer recurrence, showed that the sensitivity, specificity, and AUC-ROC for diagnosing distant metastases via PET-CT were 1.00, 0.88, and 0.98, respectively [51].…”
Section: Pet-ct and Disease Recurrencementioning
confidence: 99%